Estimation of stature from hand and handprint measurements in a monoethnic Maldivian population - Mohamed, I; Saleem, M; Zulkifly, NR; Ismail, D; Huri, MAM; Hisham, S; Mahat, NA (Taylor & Francis Ltd, 2024)
Stature estimation from anthropometric measurements of hand and handprints may prove useful in forensic investigations. Since its accuracy may be population specific, and because a similar study on the monoethnic Maldivians in Maldives remains unreported, this current research that evaluates such an aspect merits forensic significance. Using stratified-random sampling, this current research examined the standing height, as well as 22 anthropometric measurements from each hand and handprints collected from consenting 191 male and 193 female Maldivians in Maldives. Univariate and multivariate statistical analyses were used for interpreting the anthropometric measurements and their association in estimating stature. The simple linear regression analysis provided significant (p < 0.05) moderate-highly correlated (range: 0.61-0.70) regressions for hand lengths of hands and handprints of Maldivians for accurate estimation of their stature. The accuracy of the estimated stature (Standard Error of the Estimate, SEE) observed here ranged between 3.82 and 5.76 cm. Stepwise multiple regression analysis provided improved accuracy to the equation (SEE: +/- 3.78-4.45 cm). The data gathered here are the first of their kind for the Maldivians and may prove forensically relevant in crime scene investigation and disaster victim identification, a pragmatic approach for estimating stature from forensic anthropological means.